Immunomodulatory Role of Surfactant Protein-D in a Transgenic Adenocarcinoma of Mouse Prostate (TRAMP) Model - Ganguly, Kasturi; Kishore, Uday; Metkari, Siddhanath M.; Madan, Taruna (Frontiers in Immunology, 2022)
Surfactant protein D (SP-D), a potent pattern recognition molecule, is emerging as a potent anti-tumoral innate immune defense molecule in a range of cancers. Previously, SP-D expression was significantly downregulated at the malignant sites of human prostate adenocarcinoma and associated with an increasing Gleason score and severity. We recently reported selective induction of intrinsic apoptosis by a recombinant fragment of human SP-D (rfhSP-D) in the human Prostate cancer (PCa) biopsy explants and cells with glucose regulated protein of 78 (GRP78) as one of the key interacting partners. The present study evaluated the expression of SP-D in the early and advanced stages of PCa using transgenic adenocarcinoma of mouse prostate (TRAMP) model for the first time. Both early and late stage of PCa showed significantly decreased SP-D mRNA expression and increased proteolytic degradation of SP-D protein. Systemic and tumoral immunophenotyping of TRAMP revealed increased serine proteases producing granulocytes and polymorphonuclear myeloid-derived suppressor cells (PMN MDSCs) in the late stage and the serine proteases secreted by these cells could be involved in the degradation of SP-D. Susceptibility of rfhSP-D to elastase-mediated proteolysis provided the rationale to use an elastase-inhibitor to sustain intact rfhSP-D in the tumor microenvironment. The study revealed an immunomodulatory potential of rfhSP-D and elastase inhibitor, sivelestat, to induce macrophage polarization towards M1 with downregulation of PMN MDSCs in ex-vivo cultured TRAMP tumors. Furthermore, rfhSP-D induced immunogenic cell death (ICD) in murine PCa cells and in TRAMP explants. The findings highlight that SP-D plays an anti-tumorigenic role in PCa by inducing immunogenic cell death and immunomodulation while the prostate tumor milieu adversely impacts SP-D by inhibiting its transcription, and enhancing its proteolytic degradation. Transformation of an immunologically “cold tumor” into a “hot” tumor implicates therapeutic potential of rfhSP-D in PCa.